Dermatological toxicity of EGFR inhibitors: pathogenetic rationale and an algorithm for acne-like rash correction - A. V. Michenko; L. S. Kruglova; E. A. Shatokhina; I. B. Kononenko; A. S. Polonskaya; D. V. Romanov (Онкогематология)
Therapy with epidermal growth factor receptor (EGFR) inhibitors is inevitably accompanied by the phenomena of dermatological toxicity. Being, on the one hand, a favorable prognostic factor for the effectiveness of anticancer therapy, these adverse events are one of the most frequent indications for treatment withdrawal. This article presents the clinical characteristics of a wide spectrum of dermatological adverse events, as well as the pathogenetic rationale for their correction. Algorithms for prescribing of external and systemic therapy based on the assessment of severity of skin lesions and skin appendages involvement are presented.